Evaluation of groundwater sources using Electrical Resistivity Imaging (ERI) method in Felda Tersang 02, Raub, Pahang (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
This study employed the Electrical Resistivity Imaging (ERI) technique in the Felda Tersang 02 area of Raub, Pahang, to address the region's water supply issues. The study area is primarily composed of sandstone, slate, and dacite. Groundwater, critical for sustaining agricultural and industrial demands, is rapidly depleting due to unsustainable extraction. However, since the underlying geology and hydrogeology are complex, investigating and assessing groundwater sources can be challenging. By measuring the electrical resistivity of underlying materials, a geophysical technique called Electrical Resistivity Imaging (ERI) is used to map and evaluate groundwater sources. Each survey line is 200 m long with 41 takeouts spaced 5 m apart, using the Schlumberger and pole-dipole configurations. The study's findings will aid with groundwater resource management and provide a deeper understanding of the region's subsurface geology and hydrogeology. The 2D pseudosection results for all three survey lines reveal a significant accumulation of groundwater in a large geographical area. The identified low-resistivity range (0–100 Ωm) serves as a significant indicator of water-bearing formations, providing valuable insights into the area’s groundwater potential.
Keywords: groundwater sources; Electrical Resistivity Imaging (ERI); Schlumberger array configuration; 2D pseudosection; Raub; Res2Dinv software